Mutation in an Unannotated Protein Confers Carbapenem Resistance in Mycobacterium tuberculosis - Kumar, Pankaj (Antimicrob Agents Chemother, 2017)
β-Lactams are the most widely used antibacterials. Among β-lactams, carbapenems are considered the last line of defense against recalcitrant infections. As recent developments have prompted consideration of carbapenems for treatment of drug-resistant tuberculosis, it is only a matter of time before Mycobacterium tuberculosis strains resistant to these drugs will emerge. In the present study, we investigated the genetic basis that confers such resistance. To our surprise, instead of mutations in the known β-lactam targets, a single nucleotide polymorphism in the Rv2421c-Rv2422 intergenic region was common among M. tuberculosis mutants selected with meropenem or biapenem. We present data supporting the hypothesis that this locus harbors a previously unidentified gene that encodes a protein. This protein binds to β-lactams, slowly hydrolyzes the chromogenic β-lactam nitrocefin, and is inhibited by select penicillins and carbapenems and the β-lactamase inhibitor clavulanate. The mutation results in a W62R substitution that reduces the protein's nitrocefin-hydrolyzing activity and binding affinities for carbapenems.